Developing a National Data-Driven Construction Safety Management Framework with Interpretable Fatal Accident Prediction - Koc, Kerim; Ekmekcioglu, Omer; Gurgun, Asli Pelin (ASCE-AMER SOC CIVIL ENGINEERS, 2023)
Occupational accidents are frequent in the construction industry, containing significant risks in the working environment. Therefore, early designation, taking preventive actions, and developing a proactive safety risk management plan are of paramount significance in managing safety issues in the construction industry. This study aims to develop a national data-driven safety management framework based on accident outcome prediction, which helps anatomize precursors of fatalities and thereby minimizing fatal accidents on construction sites. A national data set comprising 338,173 occupational accidents recorded in the construction industry across Turkey was used to develop a data-driven model. The random forest algorithm coupled with particle swarm optimization was used for the prediction and the interpretability of the proposed model was augmented through the game theory-based Shapley additive explanations (SHAP) approach. The findings showed that the proposed algorithm achieved satisfactory model performances for detecting construction workers who might face a fatality risk. The SHAP analysis results indicated that both company (such as number of past accidents and workers in the company) and worker-related (such as age, daily wage, experience, shift, and past accident of the workers) attributes were influential in identifying fatalities by detecting which workers might face fatal accidents under which conditions. A construction safety management plan was developed based on the analysis results, which can be used on construction sites to detect workers/conditions that are most susceptible to fatalities. The findings of the present research are expected to contribute to orchestrating effective safety management practices in construction sites by characterizing the root causes of severe accidents.
Keywords: Construction safety management; Occupational accidents; Occupational health and safety (OHS); Interpretable artificial intelligence; Machine learning; RANDOM FOREST; THEORETICAL PERSPECTIVE; GENETIC ALGORITHM; BASIC QUESTIONS; FALL ACCIDENTS; SITES; INJURIES; NETWORK; HEALTH; LEVEL; Construction & Building Technology; Engineering